Penyuluhan MPASI Balita sebagai Upaya Meningkatkan Pengetahuan Ibu Balita Tentang MP ASI - Fitria Prabandari; Vistra Veftisia (Universitas Ngudi Waluyo, 2024)
The first 1000 days of life are very important because growth and development at this age are very rapid, starting from conception in the mother's womb until the child is 2 years old. At this time, there is very rapid development both in terms of the child's physical and brain. The very rapid brain development at the age of under 2 years is called the critical period of development, and is the right time to recover, if there are developmental disorders. Growth and development screening for infants is recommended every month, children aged 12-24 months are recommended every 3 months, and children aged 24-72 months are recommended every 6 months. The needs of children over 6 months are no longer met by breast milk, so children must be given complementary foods. Complementary foods is additional food that can be given to babies after reaching the age of six months to the age of 24 months. The complementary foods given must meet the child's protein and micronutrient needs. Based on the provision of Complementary Foods for Breast Milk published by IDAI in 2018, IDAI recommends 4 requirements that must be met in providing complementary foods. This activity uses a counseling method for mothers who have babies and toddlers at Posyandu RT.3 RW. 8 Kebondowo Village, Banyubiru District, Semarang Regency on November 6, 2024. Attended by 15 mothers who have babies/toddlers, 2 pregnant women, as well as cadres, and local midwives. Counseling uses flipchart media, this activity uses pretests and posttests to measure the increase in knowledge of mothers of toddlers. The results of the post-test showed an increase in knowledge of mothers of toddlers after being given health education about complementary foods. The conclusion of this activity is an increase in knowledge of mothers of toddlers about providing complementary foods. Abstrak Pada 1000 hari pertama kehidupan sangat penting karena pertumbuhan dan perkembangan pada usia ini sangat pesat, yaitu mulai dari pembuahan di dalam rahim ibu sampai anak berusia 2 tahun. Pada waktu ini terjadi perkebangan yang sangat pesat baik dari segi fisik maupun otak anak. Perkembangan otak yang sangat pesat pada usia di bawah 2 tahun ini disebut periode kritis perkembangan, dan merupakan waktu yang tepat untuk melakukan pemulihan, bila ada gangguan perkembangan. Skrining tumbuh kembang untuk bayi dianjurkan tiap bulan, anak usia 12-24 bulan dianjurkan tiap 3 bulan, dan anak usia 24-72 bulan dianjurkan tiap 6 bulan. Kebutuhan anak diatas 6 bulan sudah tidak tercukupi lagi dari ASI, sehingga anak harus diberikan makanan pendamping ASI (MPASI). MPASI merupakan makanan tambahan yang dapat diberikan kepada bayi setelah menginjak usia enam bulan hingga usia 24 bulan. MPASI yang diberikan harus memenuhi kebutuhan protein serta mikronutrien anak. Berdasarkan pemberian Makanan Pendaping ASI yang diterbitkan oleh IDAI tahun 2018, IDAI merekomendasikan 4 syarat yang harus dipenuhi dalam pemberian MPASI. Kegiatan ini menggunakan metode penyuluhan kepada ibu yang memiliki bayi dan balita di Posyandu RT.3 RW. 8 Desa Kebondowo Kecamatan Banyubiru Kabupaten Semarang pada 6 November 2024. Dihadiri oleh 15 orang ibu yang memiliki bayi/balita, 2 orang ibu hamil, serta kader, dan bidan wilayah setempat. Penyuluhan menggunakan media lembar balik, kegiatan ini menggunakan pretest dan post test untuk mengukur adanya peningkatan pengetahuan ibu balita. Hasil post test menunjukkan terjadi peningkatan pengetahuan ibu balita setelah diberikan pendidikan kesehatan tentang MP ASI. Kesimpulan dari kegiatan ini adalah meningkatnya pengetahuan ibu balita tentang pemberian MPASI.